Adaptation of mitochondrial bioenergetics to coenzyme Q deficiency in human endothelial cells after chronic exposure to bisphosphonates - Adrianna Budzinska; Lukasz Galganski; Krzysztof Wojcicki; Wieslawa Jarmuszkiewicz (Scientific Reports)
Abstract Nitrogen-containing bisphosphonates (N-BPs), widely used in bone disease therapy, inhibit the mevalonate pathway, which affects coenzyme Q (CoQ) biosynthesis and may compromise mitochondrial function, particularly in endothelial cells where oxidative stress and mitochondrial dysfunction contribute to cardiovascular disease. This study examined the effects of chronic six-day exposure of human endothelial cells to N-BPs on mitochondrial bioenergetic functions, focusing on drug-induced mitochondrial CoQ (mtCoQ) deficiency. Compared with the mitochondria of control cells, those of endothelial cells treated with 5 µM alendronate or 1 µM zoledronate presented a significant 45–50% decrease in total mtCoQ pool, loss of reduced (mtCoQH2) antioxidant mtCoQ pool, and elevated mitochondrial antioxidant protein superoxide dismutase 2 (SOD2) and uncoupling protein 2 (UCP2) levels. Exposing endothelial cells to N-BPs also led to an overall reduction in mitochondrial substrate oxidation, except for increased fatty acid oxidation. Additionally, the mitochondria of N-BP-treated endothelial cells presented decreased respiratory rates, membrane potential, and ATP synthesis efficiency, and increased H2O2 production resulting from increased mtCoQ reduction during the oxidation of complex I (CI) and CII substrates. N-BP-induced mtCoQ deficiency also resulted in rearranged respiratory chain supercomplexes, particularly downregulation of the III2 + IV supercomplex, and decreased CII, CIII, and CV protein levels and activities. Despite the N-BP-induced decrease in a-heme levels, maximal CIV activity remained unaffected in endothelial mitochondria. These findings highlight the role of N-BPs in disrupting mtCoQ redox homeostasis and associated bioenergetic functions in endothelial mitochondria.